Lithium supplement agent, electrochemical device and preparation method of lithium supplement agent
By doping Co elements in lithium-rich lithium nickelate supplementation agent and covering oxide layers of B, Al, Y, W, Ti and Si, the problem of excessive gas production in high temperature storage in batteries is solved, and the stability and kinetic performance of the lithium-added supplementation agent are improved.
Patent Information
- Application Number
- CN202311378459.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-23
- Publication Date
- 2025-04-25
AI Technical Summary
When used as lithium-rich lithium nickelate as a lithium supplement agent, the slurry processing stability is poor, resulting in excessive gas production of high-temperature storage of prepared batteries.
A lithium supplement agent is designed that includes an oxide coating layer that dopies element M1 near the surface of the lithium-rich lithium niacate matrix and coats M2 on the surface of the matrix particles. M1 includes at least Co, and M2 includes one or more of B, Al, Y, W, Ti and Si.
By doping M1 and covering the oxide layer of M2, residual alkali on the substrate surface is eliminated, structural stability is enhanced, reactivity is reduced, and gas production growth during the battery storage process is reduced.
Smart Images

Figure CN119890305A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of secondary batteries, and in particular to a lithium supplement agent, an electrochemical device and a method for preparing the lithium supplement agent. Background Art
[0002] During the first week of charging of electrochemical devices such as lithium-ion batteries, a solid electrolyte interface (SEI) is formed on the surface of the negative electrode, which consumes the active lithium in the positive electrode and causes irreversible capacity loss. The irreversible capacity loss of the most widely used graphite negative electrode can reach 10%, while for silicon-based and tin-based negative electrodes with high specific capacity, the irreversible capacity loss is even as high as 30% or more, which means that part of the active lithium released from the positive electrode material is irreversibly consumed. The loss of lithium will lead to reduced battery capacity, reduced coulombic efficiency, and poor cycle performance.
[0003] Lithium-rich nickel acid is one of the mainstream positive electrode lithium supplements currently used in the market. It can release a specific capacity of >400mAh / g during the first charge, increase the amount of active lithium in the battery cell, and improve the energy density and cycle life of the battery cell. However, the existing lithium-rich nickel acid itself has poor kinetic properties and a high residual alkalinity value. As a positive electrode lithium supplement, it not only affects the homogenization process of the battery cell slurry, but also causes excessive gas production during high-temperature storage of the prepared battery.
[0004] Therefore, it is necessary to design a lithium supplement, an electrochemical device and a method for preparing the lithium supplement to solve the above problems. Summary of the invention
[0005] In view of the above shortcomings of the prior art, the present invention provides a lithium supplement, an electrochemical device and a method for preparing the lithium supplement, so as to solve the technical problems that when the existing lithium-rich lithium nickel oxide material is used as a lithium supplement, the slurry processing stability is poor and the prepared battery produces too much gas during high-temperature storage.
[0006] To achieve the above-mentioned purpose and other related purposes, the present invention provides a lithium supplement agent, which includes a substrate and a coating layer;
[0007] Wherein, the matrix includes Li 2+a Ni 1-b M 1 b O2, where -0.2≤a≤0.1, 0.001≤b≤0.1, the M 1 including one or more of Co, B, Al, Y, W, Ti and Si; the coating layer includes M 2 The oxide, the M 2 Includes one or more of B, Al, Y, W, Ti and Si.
[0008] In an example of the present invention, the M 1 At least part of it is located on the surface of the substrate.
[0009] In an example of the present invention, the M 1 At least Co; Ni and M in the matrix 1 The molar total amount is used as the reference measurement, and the molar content of Co is 0.1% to 6%.
[0010] In an example of the present invention, the molar content of Co is 0.5% to 2.5%.
[0011] In an example of the present invention, the Co is in a lithium cobalt oxide-like phase on the surface of the substrate.
[0012] In one example of the present invention, the Ni and M in the matrix 1 The total amount of moles is the standard measurement, and the M 2 The molar content relative to the matrix is 0.1% to 4%.
[0013] In an example of the present invention, the M 2 The molar content relative to the matrix is 0.3% to 2%.
[0014] In an example of the present invention, the M 2 At least one or more of B, Al and Ti are included.
[0015] In one example of the present invention, the average particle size D50 of the lithium supplement is 0.4-40 μm.
[0016] The present invention also provides a method for preparing the lithium supplement described in any one of the above examples, the method for preparing the lithium supplement comprising:
[0017] Mixing and sintering the nickel precursor and the lithium source to obtain a first sintered material;
[0018] M is doped into the first sintered material. 1 , so that the M 1 at least partially located on the surface of the first sintered material to obtain a second sintered material;
[0019] A coating layer is formed on the surface of the second sintered material, so that the coating layer covers at least a portion of the surface of the second sintered material to obtain a lithium supplement; the coating layer is M 2 Oxide layer;
[0020] Among them, the M 1 Includes one or more of Co, B, Al, Y, W, Ti and Si; the M 2 Includes one or more of B, Al, Y, W, Ti and Si.
[0021] In one example of the present invention, the first sintered material is doped with M 1 , comprising: mixing the first sintered material with M 1 Mixed sintering of nano-precursors;
[0022] In one example of the present invention, the forming of the coating layer on the surface of the second sintered material comprises: 2 Nano-precursor mixed sintering.
[0023] The present invention also provides an electrochemical device, which includes a negative electrode plate, a positive electrode plate, a separator and an electrolyte, wherein the positive electrode plate includes a positive electrode current collector and a positive electrode active material layer, and the positive electrode active material layer includes a positive electrode material and a lithium supplement agent described in any of the above examples, or a lithium supplement agent prepared by the preparation method described in any of the above examples.
[0024] The lithium supplement agent of the present invention is doped with an element M near the surface of a lithium-rich nickelate matrix. 1 , and the surface of the lithium-rich nickel oxide matrix particles is coated with an inert element M 2 In the lithium supplement, the element M doped near the surface of the matrix particles 1 , when introduced, it can eliminate the residual alkali on the surface of the matrix, and enhance the surface conductivity and stability of the matrix particles by doping bonds. 2 The oxide coating layer can further reduce the reaction activity of the surface of the lithium supplement material, improve the interface stability of the lithium supplement, and thus reduce the gas generation of the lithium supplement during the storage of the secondary battery.
[0025] In summary, the lithium supplement provided by the present invention can enhance the structural stability of the lithium supplement while eliminating the residual alkali on the surface of the base material, improve the dynamic performance and conductivity of the lithium supplement material, improve the stability of the lithium supplement slurry process, and reduce the gas production growth of the lithium supplement during battery storage. Therefore, the present invention effectively overcomes some practical problems in the prior art and has high utilization value and use significance. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0027] Figure 1 This is a scanning electron microscope test image of the existing lithium-rich nickel oxide matrix material after two cycles of charge and discharge;
[0028] Figure 2This is a scanning electron microscope test image of a lithium supplement material in one embodiment of the present invention;
[0029] Figure 3 The figure is a schematic flow chart of a method for preparing a lithium supplement in one embodiment of the present invention. DETAILED DESCRIPTION
[0030] The following is an explanation of the embodiments of the present invention by specific examples, and those skilled in the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification. The present invention can also be implemented or applied through other different specific embodiments, and the details in this specification can also be modified or changed in various ways based on different viewpoints and applications without departing from the spirit of the present invention. It should be noted that the features in the following embodiments and the embodiments can be combined with each other without conflict. It should also be understood that the terms used in the embodiments of the present invention are intended to describe specific embodiments, rather than to limit the scope of protection of the present invention. The test methods for which specific conditions are not specified in the following examples are usually carried out under conventional conditions or according to the conditions recommended by the manufacturers.
[0031] It should be noted that the terms such as "upper", "lower", "left", "right", "middle" and "one" etc. used in this specification are only for the convenience of description and are not intended to limit the scope of implementation of the present invention. Changes or adjustments to their relative relationships, without substantially changing the technical content, should also be regarded as the scope of implementation of the present invention.
[0032] In this specification, the average particle size (D50) may be defined as the particle size corresponding to 50% of the volume accumulation in the particle size distribution curve of the particles. The average particle size (D50) may be measured, for example, by a laser diffraction method. The laser diffraction method is generally capable of measuring particle sizes ranging from the submicron range to several millimeters, thereby obtaining results with high reproducibility and high resolution.
[0033] Typically, electrochemical devices (such as secondary batteries) usually include positive electrode materials, negative electrode materials, electrolytes, diaphragms, and corresponding connecting accessories and circuits. During the battery charging and discharging process, active ions (lithium ions) are embedded and removed back and forth between the positive electrode and the negative electrode. The diaphragm is set between the positive electrode and the negative electrode, mainly to prevent the positive and negative electrodes from short-circuiting, while allowing lithium ions to pass through. The electrolyte between the positive electrode and the negative electrode mainly plays the role of conducting active ions.
[0034] During the first charge of the battery, lithium ions are released from the positive electrode active material, conducted through the electrolyte, and embedded in the negative electrode active material. During this process, some lithium ions participate in the reaction of forming a solid electrolyte interface (SEI) film on the surface of the negative electrode active material, resulting in loss of active lithium. In addition, during the subsequent cycle charge and discharge process and storage process of the battery, the repair and growth of the SEI film, as well as the side reactions of the electrolyte on the surface of the lithium-embedded negative electrode may also occur, which will irreversibly consume lithium ions. The irreversible consumption of active lithium will accelerate the decline of the battery's cycle retention rate and / or storage capacity.
[0035] The pre-lithium replenishment scheme can provide additional active lithium, thereby compensating for the loss of active lithium. In the existing lithium replenishment schemes, lithium-rich nickel oxide (Li2NiO2) is one of the mainstream positive electrode lithium replenishers, with a large first-charge gram capacity (theoretical value can release a specific capacity greater than 400mAh / g), and the first-charge lithium replenishment effect is better; however, in practical applications, using Li2NiO2 as a lithium replenisher will aggravate the gas production of the battery, especially in ternary (such as NCM) batteries, which will reduce battery performance. The reason for this is that the inventors have found that the high residual alkali value of the lithium replenisher is one of the important reasons for the high gas production of the battery prepared therefrom. During the battery charging and discharging process, the residual alkali remaining on the surface of the lithium-rich nickel oxide matrix will continue to react with the electrolyte to produce gas, and after the lithium-rich nickel oxide matrix is delithiated, lamellar active residues will remain on the surface (see the attached for details). Figure 1 ), this residue has poor electrochemical stability at the electrolyte interface and will further react with the electrolyte during the subsequent battery charge and discharge process, thereby worsening the high-temperature storage gas production of the secondary battery.
[0036] Therefore, in order to solve the above problems, the present invention provides a lithium supplement agent, which is doped with an element M near the surface of a lithium-rich nickelate matrix. 1 , and the surface of the lithium-rich nickel oxide matrix particles is coated with element M 2 The oxide coating layer is formed by doping the element M near the surface of the lithium-rich nickel oxide matrix. 1 It can effectively eliminate the residual alkali formed on the surface of lithium-rich nickel acid during the preparation process, reduce the reaction between the residual alkali on the surface of lithium-rich nickel acid and the electrolyte, enhance its own structural stability, and doping element M 1 It can also improve the electronic and ionic conductivity of lithium supplements, thereby improving the kinetic properties of lithium supplement materials. 2 The oxide coating layer can further reduce the reaction activity of the lithium supplement agent surface with the electrolyte, thereby further improving the interface stability of the lithium supplement agent surface, reducing the gas production of the lithium supplement agent with the electrolyte after delithiation, and reducing the gas production growth of the lithium supplement agent during battery storage.
[0037] The lithium supplement agent comprises a matrix and a coating layer.
[0038] The matrix includes Li2+a Ni 1-b M 1 b O2, where -0.2≤a≤0.1, 0<b<1, for example, in one example, M 1 The element composition satisfies 0.001≤b≤0.1; M 1 The element includes one or more of Co, B, Al, Y, W, Ti and Si; M 1 Elements are doped near the surface of the matrix particles, M 1 The element can eliminate the residual alkali on the surface of the matrix particles during the introduction process, so that the residual alkali value of the lithium supplement agent in the present invention (measured by Li + content) is reduced to less than 1wt%; and the structural stability of the matrix particles near the surface is enhanced by pinning bonds on the matrix surface, thereby improving the kinetic properties of the lithium supplement agent and reducing the gas generation of the side reaction of the lithium supplement agent in the secondary battery.
[0039] The coating includes M 2 Oxides of elements, M 2 The element includes one or more of B, Al, Y, W, Ti and Si. 2 When the oxide of the element is coated on the surface of the matrix particles, it can further reduce the reaction activity of the surface of the lithium supplement agent, enhance the interface stability of the lithium supplement agent, and reduce the gas generation growth rate of the lithium supplement agent in the secondary battery.
[0040] In the above lithium supplement material, the M introduced near the surface of the matrix material 1 The element can react with the residual alkali on the surface of the matrix during the doping process, thereby reducing the residual alkali retained on the surface of the matrix during preparation and enhancing the kinetic properties of the matrix. 2 The oxide coating can further reduce the reactivity of the lithium supplement surface and improve the interface stability of the lithium supplement. The above material modification can eliminate the residual alkali on the surface of the material while enhancing the interface stability, reducing the surface reactivity and reducing the side reactions with the electrolyte during the charge and discharge process, thereby improving the gas generation problem of the lithium supplement in the secondary battery.
[0041] In the matrix material Li 2+a Ni 1-b M 1 b O2, M 1 The element is selected from at least one of Co, B, Al, Y, W, Ti and Si. 1 The element may be any one of the above-listed element types, such as Co, B, Al, Y, W, Ti or Si, etc.; M 1 The element may also be any combination of two or more of the above-listed element types, for example, M1 The element can be a combination of Co and Al, or a combination of Co and B, or a combination of Co and W, or a combination of W and Si, or a combination of Al and Ti, or a combination of B and Y, or a combination of Co, Al and B, or a combination of Co, Al and W, or a combination of Co, Al, B and W, and so on, which are not listed here one by one.
[0042] In the coating layer M 2 In oxides, M 2 The element is selected from at least one of B, Al, Y, W, Ti and Si. 2 The element may be any one of the above-listed element types, such as B, Al, Y, W, Ti or Si, etc.; M 2 The element may also be any combination of two or more of the above-listed element types, for example, M 2 The element may be a combination of Al and B, or a combination of Al and Ti, or a combination of Al and W, or a combination of Ti and W, or a combination of Ti and B, or a combination of Al and Y, or a combination of W and Y, or a combination of Si and Y, or a combination of Al, B and Ti, or a combination of Si, W and Y, or a combination of Al, B, Ti, Si and Y, and so on, which are not listed here one by one.
[0043] In addition, when M 1 Elements and M 2 When the elements are two or more combinations, there is no restriction on the ratio of each element in the combination, and they can be mixed in any ratio, etc. 1 Elements and M 2 The element may be a type of element not listed above.
[0044] In the above lithium supplements, M 1 Elements are doped into the near surface of the matrix particles, where M 1 When some elements are doped, they can fully react with the residual alkali on the surface of the matrix. 1 When the element is Co, a compound phase similar to lithium cobalt oxide (referred to as lithium cobalt oxide phase) can be formed on the surface of the matrix. The lithium cobalt oxide compound phase is bonded to the near surface of the matrix particles and appears as LiNi on the near surface of the matrix particles. x Co y O 2-z , where 0<x+y≤1, z≤x, and Co in the compound phase is Co 3+ The compound phase has good electronic and ionic conductivity, which can help improve the kinetic properties of lithium supplement materials; in addition, M 1 Some elements are doped into the lattice near the surface of the matrix particles. 1Some elements can penetrate into the matrix particles near the surface to a depth of hundreds of nanometers or micrometers. 1 The inert elements replace the more active Ni elements in the near-surface lattice to enhance the interfacial stability of the lithium supplement through pinning bonds near the matrix surface.
[0045] like Figure 2 As shown, Figure 2 The scanning electron microscope schematic diagram of the lithium supplement material particles is shown. The Co element reacts with the residual alkali on the surface of the matrix and forms a lithium cobalt oxide-like compound phase near the surface of the matrix. The lithium cobalt oxide-like compound phase appears as LiNi near the surface of the matrix particles. x Co y O 2-z , where 0<x+y≤1, z≤x, and the Co element in the compound phase is Co 3+ .from Figure 2 It can be seen that under the electron microscope, there are slightly protruding moss-like particles on the surface of the lithium supplement particles. The moss-like particles are the traces left on the surface of the particles after the compound phase structure is coated.
[0046] Moreover, from the effect point of view, when the doped Co element forms the compound phase structure near the surface of the matrix, it can effectively eliminate the residual alkali on the surface of the matrix, making the residual alkali value of the lithium supplement agent itself (measured by Li + The content) is reduced to below 1wt%, thereby reducing the gas generation of the lithium supplementer in the battery due to high residual alkali. At the same time, the lithium cobalt oxide phase formed on the surface of the matrix has good electronic and ionic conductivity, which can help improve the kinetic properties of the lithium supplementer material and effectively reduce the polarization of the lithium supplementer during the first charging and de-lithiation process.
[0047] In some embodiments, M 1 The elements include at least Co. Among them, the Ni and M in the matrix 1 The molar total amount is used as the reference measurement, and the molar content of Co is 0.1% to 6%. For example, in the lithium supplement, the molar content of Co can be 0.1%, 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 4%, 5% or 6%. When the molar content of Co doped in the matrix is too high, the excess Co element will take away more active lithium in the matrix when forming a compound phase similar to lithium cobalt oxide, resulting in a reduction in the phase purity of the matrix material, resulting in a reduction in the gram capacity of the lithium supplement.
[0048] In some embodiments, the molar content of Co in the lithium supplement is preferably 0.5% to 2.5%, for example, 0.5%, 1%, 1.5%, 2% or 2.5%. When the molar content of Co in the lithium supplement is within the above range, the residual alkali value Li of the lithium supplement material itself can be + (wt %) is reduced to below 1 wt % while the gram capacity is maintained at a high level of over 400 mAh / g.
[0049] Furthermore, in the above embodiment, M 1 In addition to Co, the sintering element may also include M 2 The oxide coating is a part of the elements introduced into the near surface of the substrate material. 1 Elements other than Co may include M 2 One or more elements, for example, M 1 The elements may include at least one of B, Al, Y, W, Ti and Si in addition to Co. Further, M 1 The elements may include at least one of B, Al and Ti in addition to the Co element.
[0050] In some embodiments, the Ni and M 1 The total molar amount is used as the standard measurement, and the M added to the lithium supplement is 2 The molar content of the element is 0.1% to 4%. For example, in lithium supplements, M 2 The molar content may be 0.1%, 0.3%, 0.5%, 1%, 1.5%, 2%, 2.5%, 3% or 4%.
[0051] When the matrix particles are coated with an appropriate molar content of M 2 When the element oxide coating layer is formed, the coating layer with an appropriate molar content can improve the interface stability of the lithium supplement agent surface without excessively affecting the gram capacity and conductivity of the lithium supplement agent material, thereby improving the high-temperature storage gas production performance of the lithium supplement agent in the battery while ensuring that the addition of the lithium supplement agent does not excessively increase the DCR (Direct Current Resistance) of the battery. 2 When the molar content of the element is too high, the excess M 2 When forming a coating layer, the element will take away more active lithium in the matrix and form a Li-M with poor conductivity. 2 -O type compounds reduce the phase purity of the matrix material, resulting in a decrease in the specific capacity and conductivity of the lithium supplement material itself.
[0052] Further, in some embodiments, in the lithium supplement, the surface is coated with M 2 The molar content of the elemental oxide is preferably 0.3% to 2%, for example, it can be 0.3%, 0.4%, 0.5%, 0.7%, 0.8%, 1.0%, 1.5%, 1.7% or 2.0%.
[0053] In some embodiments, in the coating layer, M 2The elements include at least one or more of B, Al and Ti. The coating layer may be B2O3, Al2O3 or TiO2; the coating layer may also be a combination of B2O3 and Al2O3, or a combination of Al2O3 and TiO2, or a combination of B2O3 and TiO2, or a combination of Al2O3, B2O3 and TiO2.
[0054] In some embodiments, the average particle size D50 of the lithium supplement particles is 0.4 μm to 40 μm; for example, it can be 0.4 μm, 0.8 μm, 1 μm, 3 μm, 5 μm, 10 μm, 15 μm, 20 μm, 25 μm, 30 μm, 35 μm or 40 μm. When the average particle size D50 of the lithium supplement particles is within the above range, the specific surface area of the lithium supplement can be further reduced, and the occurrence of side reactions between the lithium supplement and the electrolyte can be reduced.
[0055] See also Figure 3 The present invention provides a method for preparing the lithium supplement agent described in any one of the above embodiments, comprising the following steps:
[0056] S1, mixing and sintering a nickel precursor and a lithium source to obtain a first sintered material;
[0057] S2, doping M into the first sintered material 1 , so that the M 1 at least partially located on the surface of the first sintered material to obtain a second sintered material;
[0058] S3, forming M on the surface of the second sintered material 2 an oxide coating layer, so that the coating layer covers at least a portion of the surface of the second sintered material to obtain a lithium supplement;
[0059] Among them, M 1 Includes one or more of Co, B, Al, Y, W, Ti and Si; M 2 Includes one or more of B, Al, Y, W, Ti and Si.
[0060] Step S1 specifically includes mixing the dehydrated nickel precursor and the lithium source according to a chemical dosage ratio and then sintering them under a protective atmosphere (such as N2 atmosphere) to obtain a first sintered material; the first sintered material is Li2NiO2 after sintering, and residual alkalis such as LiOH and Li2CO3 remain on the surface of the Li2NiO2 raw material. The residual alkalis such as LiOH remain on the surface of the Li2NiO2 raw material due to insufficient reaction between the nickel precursor and the lithium source.
[0061] The lithium source may include any type of water-soluble material, and may include, for example, lithium-containing sulfates, nitrates, acetates, carbonates, oxalates, citrates, halides, hydroxides or oxyhydroxides. Specifically, the lithium source may include at least one of Li2CO3, LiNO3, LiNO2, LiOH, LiOH·H2O, LiH, LiF, LiCl, LiBr, LiI, CH3COOLi, Li2O, Li2SO4, CH3COOLi or Li3C6H5O7; preferably, the lithium source may be LiOH.
[0062] The nickel precursor may include, for example, nickel-containing acetate, nitrate, sulfate, halide, sulfide, hydroxide, oxide or oxyhydroxide, and may specifically include at least one of Ni(OH)2, NiO, NiOOH, NiCO3·2Ni(OH)2·4H2O, NiC2O2·2H2O, Ni(NO3)2·6H2O, NiSO4, NiSO4·6H2O, fatty acid nickel salt or nickel halide, but is not limited thereto. Preferably, the nickel source may be Ni(OH)2.
[0063] Step S2 specifically includes crushing the first sintered material and mixing it with M 1 The nano precursor material is mixed and then sintered in a protective atmosphere (such as N2 atmosphere) to obtain a second sintered material. 1 The nano precursor reacts with the residual alkali LiOH on the surface of the first sintered material, M 1 The first sintered material is doped near the surface through reaction, thereby reducing the residual alkali on the surface of the first sintered material and enhancing the kinetic performance of preparing the lithium supplement.
[0064] Among them, M 1 The nano precursor may include M 1 The acetate, nitrate, sulfate, halide, sulfide, hydroxide, oxide or oxyhydroxide of the element. 1 The element at least includes Co element. When the Co nano precursor is sintered, it reacts with the surface residual alkali LiOH to form a compound phase structure similar to lithium cobalt oxide near the surface of the first sintered material particle. The compound phase structure is bonded to the near surface of the matrix particle and forms a LiNi x Co y O 2-z The form exists, where 0<x+y≤1, z≤x, and the Co element in the compound phase is Co 3+ The Co precursor may include Co3O4, CoOOH, Co(OCOCH3)2·4H2O, Co(NO3)2·6H2O, CoSO4 or Co(SO4)2·7H2O, but is not limited thereto. Preferably, the Co precursor may be Co3O4 or CoOOH.
[0065] In step S2, the Ni and M in the lithium supplementation agent matrix are prepared. 1 The total molar amount is the standard measurement, and the added M 1 The nano precursor accounts for 0.1% to 10% of the prepared lithium supplement matrix by mole, preferably 0.5% to 6%; that is, the added M 1 The mass percentage of the nano precursor in the lithium supplement is 0.5wt% to 9wt%, preferably 0.5wt% to 5.3wt%.
[0066] Step S3 specifically includes crushing the second sintered material and mixing it with M 2 The nano-precursor materials are mixed and sintered in a protective atmosphere (such as N2 atmosphere) to make M 2 The elements are sintered on the surface of the second sintered material to form a coating layer, thereby obtaining a lithium supplement.
[0067] In step S3, the Ni and M in the lithium supplementation agent matrix are prepared. 1 The total molar amount is the standard measurement, and the added M 2 The molar percentage of the nano precursor in the prepared lithium supplementing agent matrix is 0.1% to 4%, preferably 0.3% to 2%.
[0068] The present invention also provides an electrochemical device, which can be a solid lithium ion secondary battery or a liquid lithium ion secondary battery. Taking a liquid lithium ion secondary battery as an example, the electrochemical device includes a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte disposed between the positive electrode sheet and the negative electrode sheet, the positive electrode sheet includes a positive electrode current collector and a positive electrode active material layer disposed on the positive electrode current collector, the positive electrode active material layer includes a positive electrode material, a conductive agent, a binder and a lithium supplement agent described in any of the above embodiments, or a lithium supplement agent prepared by the preparation method described in any of the above embodiments; the negative electrode sheet includes a negative electrode current collector and a negative electrode active material layer disposed on the negative electrode current collector, the negative electrode active material layer includes a negative electrode material, a conductive agent, a thickener and a binder. Among them, the positive and negative electrode materials can deintercalate and deintercalate lithium ions to achieve energy storage and release. The electrolyte is the carrier for the transmission of lithium ions between the positive and negative electrodes. The diaphragm can pass lithium ions but is not conductive, thereby separating the positive and negative electrodes to prevent short circuits. The positive electrode lithium replenisher can deintercalate lithium ions before the positive electrode active material during the first charging process of the electrochemical device, so as to compensate for the lithium ions consumed by the formation of SEI on the surface of the negative electrode material during the first charging of the negative electrode plate, thereby compensating for the coulomb efficiency loss of the positive and negative electrode plates in the first cycle and maintaining the capacity of the electrochemical device.
[0069] In some embodiments, the mass content of the lithium supplement agent in the positive electrode active material layer is 0.1-10wt%, for example, it can be 0.1wt%, 0.5wt%, 1wt%, 2wt%, 3wt%, 4wt%, 5wt%, 6wt%, 7wt%, 8wt%, 9wt% or 10wt%; preferably, the mass content of the lithium supplement agent in the positive electrode active material layer is 2-7wt%, for example, it can be 2wt%, 2.5wt%, 3wt%, 3.5wt%, 4wt%, 4.5wt%, 5wt%, 5.5wt%, 6wt%, 6.5wt% or 7wt%. When the mass content of the lithium supplement agent in the positive electrode active material layer is within the above range, the loss of active lithium in the positive electrode active material layer can be compensated as much as possible without excessively affecting the energy density of the battery. Among them, when the mass content of the lithium supplement agent is lower than the above range, it may not be able to make up for the loss of active lithium in the positive electrode active material layer; when the mass content of the lithium supplement agent is higher than the above range, it may cause insufficient reversible lithium insertion vacancies in the positive electrode active material layer, affecting the energy density of the battery.
[0070] It should be noted that the preparation of the positive electrode sheet, negative electrode sheet, separator, electrolyte and the assembly process of the electrochemical device can be prepared by conventional methods in the art. For example, the preparation process of the positive electrode sheet is as follows: the positive electrode material, lithium supplement, conductive agent and binder are mixed in a mass ratio of (87 to 97): (0.1 to 10): 1.5: 1.5, preferably a mass ratio of 94: 3: 1.5: 1.5, and the solvent N-methylpyrrolidone (NMP) is added, and the mixture is stirred thoroughly to obtain a positive electrode slurry; the positive electrode slurry is coated on the positive electrode current collector aluminum foil, and the positive electrode sheet is prepared through drying, cold pressing, slitting and other processes. Among them, the positive electrode material can be selected from lithium cobalt oxide, ternary materials and lithium-containing phosphates. Specifically, the ternary materials include but are not limited to lithium nickel cobalt manganese oxide LiNi x Co y Mn z O2 (x+y+z=1); lithium-containing phosphates include but are not limited to lithium iron manganese phosphate, lithium iron phosphate, lithium manganese phosphate, etc. The conductive agent can be selected from at least one of carbon black (Super P), acetylene black, carbon nanotubes (CNT), graphene, nano carbon fiber (VGCF) and other conductive materials, for example, the conductive agent is SP and CNT, and the mass ratio of SP to CNT is 1:0.5. The binder can be selected from at least one of PVDF, PTFE, etc.
[0071] The technical scheme of the present invention is described in detail below through several specific examples and comparative examples. Unless otherwise specified, the raw materials and reagents used in the following examples are commercially available products or can be prepared by conventional methods in the art.
[0072] Example 1
[0073] This embodiment provides a lithium supplement agent, which includes Li 2.005 Ni 0.995 Co 0.005 O2 matrix and Al2O3 coating layer coated on the surface of matrix particles. The preparation method of the lithium supplement agent is as follows:
[0074] S1, uniformly mixing the dehydrated Ni(OH)2 precursor and LiOH according to the chemical dosage ratio, sintering at 800°C in a N2 atmosphere for 20 hours to obtain a first sintered material;
[0075] S2, crushing the first sintered material, mixing the crushed first sintered material with nano-CoOOH, sintering the mixture at 800°C in N2 atmosphere for 10 hours to obtain a second sintered material; wherein the Ni and M in the lithium supplementing agent matrix 1 The total molar amount (i.e. 1 / 2 of the molar amount of O in the matrix) is used as the reference measurement, and nano-CoOOH with a Co molar content of 0.5% is added;
[0076] S3, crushing the second sintered material, mixing the crushed second sintered material with nano-Al2O3, sintering the mixture at 400°C in N2 atmosphere for 8 hours to obtain a lithium supplement; wherein the Ni and M in the lithium supplement matrix 1 The total molar amount (i.e., 1 / 2 of the molar amount of O in the matrix) is used as the reference measurement, and nano-Al2O3 with an Al molar content of 0.39% is added.
[0077] Example 2
[0078] This example prepares a lithium supplement material with the same system as that of Example 1. The lithium supplement material includes Li 2.011 Ni 0.99 Co 0.01 O2 matrix and Al2O3 coating layer coated on the surface of the matrix particles. The difference between this embodiment and embodiment 1 is that in step S2, nano-CoOOH with a Co molar content of 1% is added.
[0079] Example 3
[0080] This example prepares a lithium supplement material with the same system as that of Example 1. The lithium supplement material includes Li 2.015 Ni 0.985 Co 0.015 O2 matrix and Al2O3 coating layer coated on the surface of the matrix particles. The difference between this embodiment and embodiment 1 is that in step S2, nano-CoOOH with a Co molar content of 1.5% is added.
[0081] Example 4
[0082] This example prepares a lithium supplement material with the same system as that of Example 1. The lithium supplement material includes Li 2.019 Ni 0.98 Co 0.02 O2 matrix and Al2O3 coating layer coated on the surface of the matrix particles. The difference between this embodiment and embodiment 1 is that in step S2, nano-CoOOH with a Co molar content of 2% is added.
[0083] Example 5
[0084] This example prepares a lithium supplement material with the same system as that of Example 1. The lithium supplement material includes Li 2.025 Ni 0.975 Co 0.025 O2 matrix and Al2O3 coating layer coated on the surface of the matrix particles. The difference between this embodiment and embodiment 1 is that: in step S2, nano-CoOOH with a Co molar content of 2.5% is added.
[0085] Example 6
[0086] This example prepares a lithium supplement material with the same system as that of Example 1. The lithium supplement material includes Li 2.03 Ni 0.97 Co 0.03 O2 matrix and Al2O3 coating layer coated on the surface of the matrix particles. The difference between this embodiment and embodiment 1 is that: in step S2, nano-CoOOH with a Co molar content of 3% is added.
[0087] Example 7
[0088] This example prepares a lithium supplement material with the same system as that of Example 1. The lithium supplement material includes Li 2.03 Ni 0.94 Co 0.06 O2 matrix and Al2O3 coating layer coated on the surface of the matrix particles. The difference between this embodiment and embodiment 1 is that: in step S2, nano-CoOOH with a Co molar content of 6% is added.
[0089] Example 8
[0090] This example prepares a lithium supplement material with the same system as that of Example 4. The lithium supplement material includes Li 2.03 Ni 0.97 Co 0.03 O2 matrix and Al2O3 coating layer coated on the surface of the matrix particles. The difference between this embodiment and embodiment 4 is that: in step S3, nano-Al2O3 with Al molar content of 0.06% is added.
[0091] Example 9
[0092] This example prepares a lithium supplement material with the same system as that of Example 4. The lithium supplement material includes Li 2.019 Ni 0.98 Co 0.02 O2 matrix and Al2O3 coating layer coated on the surface of the matrix particles. The difference between this embodiment and embodiment 4 is that: in step S3, nano-Al2O3 with Al molar content of 0.77% is added.
[0093] Example 10
[0094] This example prepares a lithium supplement material with the same system as that of Example 4. The lithium supplement material includes Li 2.019 Ni 0.98 Co 0.02 O2 matrix and Al2O3 coating layer coated on the surface of the matrix particles. The difference between this embodiment and embodiment 4 is that: in step S3, nano-Al2O3 with Al molar content of 1.55% is added.
[0095] Embodiment 11
[0096] This example prepares a lithium supplement material with the same system as that of Example 4. The lithium supplement material includes Li 2.019 Ni 0.98 Co 0.02 O2 matrix and Al2O3 coating layer coated on the surface of the matrix particles. The difference between this embodiment and embodiment 4 is that: in step S3, nano-Al2O3 with Al molar content of 2% is added.
[0097] Example 12
[0098] This example prepares a lithium supplement material with the same system as that of Example 4. The lithium supplement material includes Li 2.019 Ni 0.98 Co 0.02 O2 matrix and TiO2 coating layer coated on the surface of the matrix particles. The difference between this embodiment and embodiment 4 is that: in step S3, nano-TiO2 with a Ti molar content of 0.33% is added.
[0099] Embodiment 13
[0100] This example prepares a lithium supplement material with the same system as that of Example 4. The lithium supplement material includes Li 2.019 Ni 0.98 Co 0.02 O2 matrix and Al2O3 and B2O3 composite coating layer coated on the surface of the matrix particles. The difference between this embodiment and embodiment 4 is that in step S3, nano Al2O3 with Al molar content of 0.19% and nano B2O3 with B molar content of 0.32% are added.
[0101] Embodiment 14
[0102] This example prepares a lithium supplement material with the same system as that of Example 4. The lithium supplement material includes Li 2.019 Ni 0.98 Co 0.02 O2 matrix and Al2O3 and WO3 composite coating layer coated on the surface of the matrix particles. The difference between this embodiment and embodiment 4 is that in step S3, nano Al2O3 with an Al molar content of 0.19% and nano WO3 with a W molar content of 0.13% are added.
[0103] Comparative Example 1
[0104] Comparative Example 1 provides a lithium supplement, which only contains a Li2NiO2 matrix. The preparation method of Li2NiO2 in this comparative example refers to Example 4. The difference between it and Example 4 is that the preparation method does not include step S3, and nano-CoOOH is not added in step S2.
[0105] Comparative Example 2
[0106] Comparative Example 2: A lithium supplement material having the same system as that of Example 4 was prepared. The lithium supplement material only included Li 2.019 Ni 0.98 Co 0.02 O2 matrix, but not including the coating layer on the surface of the matrix particles. The difference between this comparative example and Example 4 is that the preparation method does not include step S3.
[0107] The lithium supplements prepared in Examples 1 to 12 and Comparative Examples 1 to 2 were respectively assembled into lithium ion secondary batteries to verify the efficacy of the present invention. The preparation process of the secondary battery is as follows:
[0108] (1) Preparation of positive electrode sheet: The positive electrode material LiNi 0.8 Co 0.1 Mn 0.1 O2 is mixed with the lithium supplement agent, conductive agent carbon black (Super P), and binder polyvinylidene fluoride (PVDF) prepared above in a weight ratio of 94:3:1.5:1.5, and solvent N-methylpyrrolidone (NMP) is added, and the mixture is stirred thoroughly to obtain a positive electrode slurry; the mixture is stirred under the action of a vacuum mixer until the system is uniform and transparent to obtain a positive electrode slurry. The positive electrode slurry is evenly coated on a 16μm aluminum foil current collector, and then the aluminum foil current collector is dried at room temperature and transferred to an oven to dry at 80℃~120℃ for 6h, and then cold pressed and cut to obtain a positive electrode sheet.
[0109] (2) Preparation of negative electrode sheets: negative electrode material graphite, conductive agent acetylene black, thickener sodium carboxymethyl cellulose (CMC) and binder styrene butadiene rubber (SBR) were mixed in a mass ratio of 96.4:1:1.2:1.4, deionized water was added, and the solid content of the slurry was adjusted to 55%, and then the mixture was fully stirred and mixed under the action of a vacuum mixer to obtain a negative electrode slurry; the negative electrode slurry was evenly coated on both sides of an 8 μm negative electrode current collector copper foil; after drying at room temperature, the mixture was transferred to an oven for drying, and then cold pressed, cut and other processes were performed to obtain a negative electrode sheet.
[0110] (3) Preparation of electrolyte: In an argon atmosphere glove box with a water content of <10 ppm, ethylene carbonate (EC), ethyl methyl carbonate (EMC), and diethyl carbonate (DEC) were uniformly mixed in a volume ratio of 1:1:1 to obtain an organic solvent. Then, fully dried lithium salt LiPF6 was dissolved in the mixed organic solvent to prepare an electrolyte with a concentration of 1 mol / L.
[0111] (4) Diaphragm preparation: The diaphragm is a 9 μm polyethylene diaphragm coated on both sides with a ceramic coating with a thickness of 2 μm.
[0112] (5) Assembling the battery: The positive electrode sheet, separator, and negative electrode sheet prepared above are stacked in sequence, with the separator placed between the positive and negative electrode sheets to play a role of isolation. Then, the sheet is wrapped with aluminum plastic film, transferred to a vacuum oven for drying at 120°C, and sealed after injecting 3.0g / Ah of electrolyte. After standing, hot and cold pressing, formation, clamping, and capacity division, a soft-pack battery (i.e., lithium-ion battery) with a capacity of 1Ah is finally prepared.
[0113] The specific steps and conditions for electrolyte formation are as follows: after the electrolyte is injected, maintain a hot pressure environment of 0.1MPa, charge at 0.02C for 17min at 45°C in a static state, stand for 5min and then charge to 0.3Ah at 0.02C, then cut off the air bag and vacuum seal, and stand at room temperature for 48h to complete the electrolyte formation.
[0114] The test results are shown in Table 1, and the test method is as follows:
[0115] (1) Test of residual alkali value of lithium supplement:
[0116] According to GB / T 41704-2022 method, the residual alkali content is tested and the free Li in the lithium supplement powder is calculated. + Quality content.
[0117] (2) Viscosity rebound test of lithium supplement slurry after standing for 30 minutes:
[0118] The single cylinder rotation viscometer method of GB / T 2794-2022 was used to test the viscosity of the lithium supplement slurry. The initial viscosity P1 of the lithium supplement slurry was measured first, and then the lithium supplement slurry was placed at room temperature for 30 minutes and the viscosity P2 of the slurry after standing was measured. The viscosity rebound rate of the lithium supplement slurry after standing for 30 minutes was calculated as (P1-P2) / P1.
[0119] (3) Gas production performance test of soft pack battery:
[0120] The initial volume V1 of the secondary battery prepared above was tested after full charging, and then the secondary battery was stored in a high temperature cabinet at 60°C. The secondary battery was recharged and the volume was tested every 7 days. After 56 days, the volume of the secondary battery tested was V2, and (V2-V1) / V1 was the gas production growth.
[0121] (4) Soft pack battery DCR test method:
[0122] The capacity of the secondary battery (cell after capacity division) prepared above was adjusted to 50% SOC (State Of Charge), and then the DCR of the secondary battery was tested by discharging at a constant current rate of 4C for 30s.
[0123] (5) Lithium supplement capacity test:
[0124] The prepared lithium supplement material, conductive agent Super P, and binder polyvinylidene fluoride (PVDF) are mixed in a weight ratio of 85:10:5, and a solvent N-methylpyrrolidone (NMP) is added, and the mixture is stirred to obtain a positive electrode slurry; the positive electrode slurry is coated on a positive electrode current collector aluminum foil, and a positive electrode plate is prepared through drying, cold pressing, slitting, and other processes, and a 2032 button half-cell is assembled using lithium metal as a negative electrode plate;
[0125] At 25°C, the half-button battery was subjected to the first charge and discharge test at a current density of 0.02A / g in the test voltage range of 3V (discharge cut-off voltage) to 4.3V (charge cut-off voltage). The charge / discharge capacity of the half-button battery was measured and then divided by the mass of the lithium supplement to obtain the gram capacity of the lithium supplement.
[0126] The performance test results of the lithium supplement agents and the corresponding assembled secondary batteries in Examples 1 to 12 and Comparative Examples 1 to 2 are shown in Table 1.
[0127] Table 1: Parameters and performance test results of the lithium supplements and the corresponding assembled secondary batteries in Examples 1 to 12 and Comparative Examples 1 to 2.
[0128]
[0129]
[0130] Comparing the test results of Examples 1 to 7 and Comparative Examples 1 to 2, it can be seen that the Co element introduced during the secondary sintering of the lithium-rich nickel oxide can form doping near the surface of the lithium-rich nickel oxide, consume residual alkali and form a lithium cobalt oxide-like phase, effectively reducing the residual alkali value of the lithium supplement (free Li + The content is reduced to less than 1wt%), and the static viscosity rebound reduction rate of the slurry is greatly reduced, thereby improving the kinetic performance of the lithium supplement and the storage gas production growth of the secondary battery equipped with the lithium supplement. At the same time, since the residual alkali with high electronic impedance on the surface of the lithium supplement is replaced by a lithium cobalt oxide-like phase with good kinetic performance, the DCR of the secondary battery is also reduced.
[0131] As shown in the test results of Example 3 and Comparative Example 1, after adding 1.51 mol% of Co to the lithium supplement material, the residual alkali value of the lithium supplement material decreased by half compared with that before doping, the static viscosity rebound of the slurry decreased by 35%, and the gas production growth rate of the assembled secondary battery after 56 days of storage decreased by 54%, and the DCR also decreased by 13.5%. It can be seen that doping Co in the lithium supplement matrix can improve the comprehensive performance of the assembled secondary battery.
[0132] Comparing the test results of Example 4 and Comparative Example 2, it can be seen that the substrate coated with inert metal oxides helps to further eliminate the residual alkali on the surface of the lithium supplement agent and improve the interface stability of the lithium supplement agent, thereby reducing the storage gas production growth rate and DC internal resistance of the assembled secondary battery. Specifically, as shown in the test results of Example 4 and Comparative Example 2, after the lithium supplement agent substrate is coated with the Al2O3 coating layer, the residual alkali value of the lithium supplement agent is reduced by 38%, the static viscosity rebound of the slurry is reduced by 34%, and the gas production growth rate of the assembled secondary battery after 56 days of storage is reduced by 42%, and the DCR is also reduced by 12%.
[0133] Comparing the test results of Examples 1 to 7, it can be seen that within the appropriate addition range, as the molar content of the doped Co element increases, the residual alkali value and static viscosity rebound rate of the lithium supplement agent itself are further reduced, and the high-temperature storage gas generation of the assembled secondary battery is also reduced. However, when the molar content of the doped Co element in the lithium supplement agent is too high, the excessive Co element will consume excessive Li in the matrix. + , resulting in a decrease in the purity and gram capacity of the lithium supplement agent. At the same time, some residual alkali on the surface of the lithium supplement agent was not consumed because a large amount of Co elements entered the matrix to replace the Ni element, resulting in a decrease in the effect of excessive Co doping on eliminating the residual alkali value of the lithium supplement agent. The corresponding high-temperature storage gas production of the assembled secondary battery also increased accordingly.
[0134] Specifically, when the molar content of the doped Co element in the lithium supplement is in the suitable addition range of 0.5% to 2.5%, the residual alkalinity value of the lithium supplement itself decreases with the increase of the molar content of the doped Co element, and the high-temperature storage gas production of the corresponding assembled secondary battery also decreases accordingly; but when the molar content of the doped Co element in the lithium supplement is higher than 2.5%, the residual alkalinity value of the lithium supplement itself increases and deteriorates with the increase of the molar content of the doped Co element, and the high-temperature storage gas production of the corresponding assembled secondary battery increases accordingly.
[0135] Comparing the test results of Example 4 and Examples 8 to 11, it can be seen that as the molar content of the coated Al element increases, the gram capacity of the lithium supplement agent itself decreases to a certain extent, but at the same time, the residual alkali value and static viscosity rebound rate of the lithium supplement agent will also decrease, and the high-temperature storage gas generation of the corresponding assembled secondary battery will also be further reduced. However, when the molar content of the Al element coated on the surface of the lithium supplement agent is too high, too much Al coating will take away the Li in the matrix. + , forming Li-Al-O compounds with poor conductivity on the surface of the lithium supplement, causing the lithium supplement's gram capacity to further decrease and increasing the DCR of the corresponding assembled secondary battery.
[0136] Comparing the test results of Examples 4, 12, 13 and 14, it can be seen that coating the surface of the lithium supplement with an appropriate amount of inert oxides of elements such as Al, B, W and Ti can further improve the high-temperature storage gas production growth of the secondary battery, so that the gas production growth rate of the corresponding assembled secondary battery after 56 days of storage is maintained below 15%.
[0137] In summary, the lithium supplement material provided by the present invention eliminates residual alkali on the surface of the lithium supplement matrix and improves the kinetic properties of the matrix by adding and regulating the doping amount of the Co element during the secondary sintering, and coats the surface of the lithium supplement with inert metal oxides through the tertiary sintering to further reduce the surface activity of the lithium supplement, improve the interface stability and processing performance of the lithium supplement, thereby comprehensively improving the high-temperature storage gas production and rate performance of the secondary battery.
[0138] The above embodiments are merely illustrative of the principles and effects of the present invention, and are not intended to limit the present invention. Anyone familiar with the art may modify or alter the above embodiments without departing from the spirit and scope of the present invention. Therefore, all equivalent modifications or alterations made by a person of ordinary skill in the art without departing from the spirit and technical concept disclosed by the present invention shall still be covered by the claims of the present invention.
Claims
1. A lithium supplement, characterized in that: include: A matrix comprising Li 2+a Ni 1-b M 1 b O2, where -0.2≤a≤0.1, 0.001≤b≤0.1, the M 1 including one or more of Co, B, Al, Y, W, Ti and Si; The coating layer comprises M 2 The oxide, the M 2 Includes one or more of B, Al, Y, W, Ti and Si.
2. The lithium supplement according to claim 1, characterized in that: The M 1 At least part of it is located on the surface of the substrate.
3. The lithium supplement according to claim 1 or 2, characterized in that: The M 1 At least Co; Ni and M in the matrix 1 Based on the total molar amount as the reference measurement, the molar content of Co is 0.1% to 6%; further, the molar content of Co is 0.5% to 2.5%.
4. The lithium supplement according to claim 3, characterized in that: The Co is in a lithium cobalt oxide-like phase on the surface of the substrate.
5. The lithium supplement according to claim 1, characterized in that: The Ni and M in the matrix 1 The total amount of moles is the standard measurement, and the M 2 The molar content relative to the matrix is 0.1% to 4%; further, the M 2 The molar content relative to the matrix is 0.3% to 2%.
6. The lithium supplement according to claim 1, characterized in that: The M 2 At least one or more of B, Al and Ti are included.
7. The lithium supplement according to claim 1, characterized in that: The average particle size D50 of the lithium supplement agent is 0.4-40 μm.
8. A method for preparing the lithium supplement according to any one of claims 1 to 7, characterized in that: include: Mixing and sintering the nickel precursor and the lithium source to obtain a first sintered material; Doping M into the first sinter 1 , so that the M 1 at least partially located on the surface of the first sintered material to obtain a second sintered material; A coating layer is formed on the surface of the second sintered material, so that the coating layer covers at least a portion of the surface of the second sintered material to obtain a lithium supplement; the coating layer is M 2 Oxide layer; Among them, the M 1 Includes one or more of Co, B, Al, Y, W, Ti and Si; the M 2 Includes one or more of B, Al, Y, W, Ti and Si.
9. The preparation method according to claim 8, characterized in that: The first sintered material is doped with M 1 , comprising: mixing the first sintered material with M 1 Mixed sintering of nano-precursors; and / or, The forming of the coating layer on the surface of the second sintered material comprises: 2 Nano-precursor mixed sintering.
10. An electrochemical device, characterized in that: The invention comprises a negative electrode sheet, a positive electrode sheet, a separator and an electrolyte, wherein the positive electrode sheet comprises a positive electrode current collector and a positive electrode active material layer, and the positive electrode active material layer comprises a positive electrode material and the lithium supplement agent according to any one of claims 1 to 7, or a lithium supplement agent prepared by the preparation method according to claim 8 or 9.